The Agenda of Wearable Healthcare - Tröster, G. (Yearbook of Medical Informatics, 2005)
Driven by cost and quality issues, the health system in the developed countries will undergo a fundamental change in this decade, from a physician-operated and hospital centred health system to consumer operated personal prevention, early risk detection and wellness system. This paper sketches the vision of a ‘Personal Health Assistant’ PHA, opening up new vistas in patient centred healthcare. The PHA comprises a wearable sensing and communicating system, seamlessly embedded in our daily outfit. Several onbody sensors identify the biometric and contextual status of the wearer continuously. The embedded computer generates the ‘Life Balance Factor’ LBF as an individual feedback to the user and to the surroundings affording an effective prevention, disease management and rehabilitation also in telemedicine. The state-of-the-art enabling technologies – mainly miniaturization of electronics and sensors combined with wireless communication and recent developments in wearable and pervasive computing are presented and assessed concerning multiparameter health monitoring.